Genomic Characterization of Multidrug-Resistant Escherichia coli BH100 Sub-strains - Carvalho, Rodrigo; Aburjaile, Flavia; Canario, Marcus; Nascimento, Andréa M. A.; Chartone-Souza, Edmar; de Jesus, Luis; Zamyatnin, Andrey A.; Brenig, Bertram; Barh, Debmalya; Ghosh, Preetam; Goes-Neto, Aristoteles; Figueiredo, Henrique C. P.; et al. (Frontiers in Microbiology, 2021)
The rapid emergence of multidrug-resistant (MDR) bacteria is a global health problem. Mobile genetic elements like conjugative plasmids, transposons and integrons are the major players in spreading resistance genes in uropathogenic E. coli (UPEC) pathotype. The E. coli BH100 strain was isolated from the urinary tract of a Brazilian woman in 1974. This strain presents two plasmids carrying MDR cassettes, pBH100 and pAp, with conjugative and mobilization properties, respectively. However, its transposable elements have not been characterized. In this study, we attempted to unravel the factors involved in the mobilization of virulence and drug-resistance genes by assessing genomic rearrangements in four BH100 sub-strains (BH100 MG2014, BH100 MG2017, BH100L MG2017, and BH100N MG2017). Therefore, the complete genomes of the BH100 sub-strains were achieved through Next Generation Sequencing and submitted to comparative genomic analyses. Our data shows recombination events between the two plasmids in the sub-strain BH100 MG2017 and between pBH100 and the chromosome in BH100L MG2017. In both cases, IS3 and IS21 elements were detected upstream of Tn21 family transposons associated with MDR genes at the recombined region. These results integrated with Genomic island analysis suggest pBH100 might be involved in the spreading of drug resistance through the formation of resistance islands. Regarding pathogenicity, our results reveal that BH100 strain is closely related to UPEC strains and contains many IS3 and IS21-transposase-enriched genomic islands associated with virulence. This study concludes that those IS elements are vital for the evolution and adaptation of BH100 strain.